2020
DOI: 10.1080/13621718.2020.1747198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intermetallics on susceptibility of Mg alloy welds to liquation cracking

Abstract: The circular-patch welding test was used to study the liquation and liquation cracking of AZseries Mg alloys. A heat treatment was carried out on the as-received AZ91 alloy to dissolve the γ (Mg 17 Al 12 ) particles before welding. The circular-patch welding test was then conducted on the heat-treated, as-received AZ91 alloy using AZ61 and AZ91 filler wires. The results showed that the susceptibility of AZ91 alloy to liquation and liquation cracking was significantly reduced by the dissolution of massive γ (Mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… Modification of as-cast microstructure via a post casting/pre-welding homogenisation: Thermal treatment of cast alloys aiming at the dissolution of second phase particles can enhance the resistance to liquation during welding. It is shown that using a prolonged homogenisation treatment before welding of AZ91 can reduce the volume fraction of eutectic Mg 17 Al 12 , which in turn can eliminate the possibility of constitutional liquation mechanism [138] Modification of as-cast microstructure via a friction stir processing (FSP) as a pre-welding treatment: In the situation where there is no possibility to produce a crack-resistance microstructure during the manufacturing process (e.g. casting) within the bulk material, friction stir processing (FSP) can be utilised as a successful strategy for local microstructural modification of the base metal before the welding [139].…”
Section: Liquation and Liquation Cracking Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“… Modification of as-cast microstructure via a post casting/pre-welding homogenisation: Thermal treatment of cast alloys aiming at the dissolution of second phase particles can enhance the resistance to liquation during welding. It is shown that using a prolonged homogenisation treatment before welding of AZ91 can reduce the volume fraction of eutectic Mg 17 Al 12 , which in turn can eliminate the possibility of constitutional liquation mechanism [138] Modification of as-cast microstructure via a friction stir processing (FSP) as a pre-welding treatment: In the situation where there is no possibility to produce a crack-resistance microstructure during the manufacturing process (e.g. casting) within the bulk material, friction stir processing (FSP) can be utilised as a successful strategy for local microstructural modification of the base metal before the welding [139].…”
Section: Liquation and Liquation Cracking Phenomenamentioning
confidence: 99%
“… Modification of as-cast microstructure via a post casting/pre-welding homogenisation: Thermal treatment of cast alloys aiming at the dissolution of second phase particles can enhance the resistance to liquation during welding. It is shown that using a prolonged homogenisation treatment before welding of AZ91 can reduce the volume fraction of eutectic Mg 17 Al 12 , which in turn can eliminate the possibility of constitutional liquation mechanism [138] …”
Section: Liquation and Liquation Cracking Phenomenamentioning
confidence: 99%
“…Therefore, the deleterious effect of PMZ on the joint performance remains unchanged. In order to improve the resistance to liquation, Yuan et al [7] performed a pre-weld heat treatment to dissolve eutectic β-Mg 17 Al 12 in the as-cast AZ91. They showed that this technique is successful in eliminating constitutional liquation.…”
Section: Introductionmentioning
confidence: 99%
“…However, this alloy presents some metallurgical challenges during fusion welding, as a key manufacturing process as well as a viable repair technology. AZ91 exhibits high resistance to solidification cracking, however [4], it is highly susceptible to liquation cracking during fusion welding [5,6]. Liquation cracking in the weld is due to the formation of grain boundary liquid and the inability of the liquid films to support tensile stresses which develop during weld cooling [7].…”
Section: Introductionmentioning
confidence: 99%